2005
DOI: 10.1007/s00221-004-2201-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the plane of regard in space

Abstract: When we fixate an object in space, the rotation centers of the eyes, together with the object, define a plane of regard. People perceive the elevation of objects relative to this plane accurately, irrespective of eye or head orientation (Poljac et al. (2004) Vision Res, in press). Yet, to create a correct representation of objects in space, the orientation of the plane of regard in space is required. Subjects pointed along an eccentric vertical line on a touch screen to the location where their plane of regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…RMSE values, computed as in the preceding text, yielded 3.1 vs. 12.7 and 4.7 vs. 14.3°(retinal vs. nonretinal model) for the rightward and the leftward dynamic gaze changes, respectively. This corroborates findings in previous literature that also made a clear case for the retinal coding and updating of target direction (Henriques et al 1998;Poljac and Van den Berg 2003).…”
Section: Reach Patternssupporting
confidence: 92%
“…RMSE values, computed as in the preceding text, yielded 3.1 vs. 12.7 and 4.7 vs. 14.3°(retinal vs. nonretinal model) for the rightward and the leftward dynamic gaze changes, respectively. This corroborates findings in previous literature that also made a clear case for the retinal coding and updating of target direction (Henriques et al 1998;Poljac and Van den Berg 2003).…”
Section: Reach Patternssupporting
confidence: 92%
“…a downward bias of reaching errors that was modulated by both target eccentricity and performing hand. Other studies on goal-directed arm-movements showed an overall vertical undershoot of the target position [1], [5], [30], [49], which can be due to a bias toward initial hand position [24] or, more likely, to an interference with the visuomotor transformation by sustained tonus in arm muscles when the arm is raised [49]. Whereas the former hypothesis cannot account for our pattern of errors, since we did not find any bias toward initial hand position in the horizontal component of reaching errors (i.e., an undershoot, instead of an overshoot, in reaching peripheral targets), the latter hypothesis fits better with our results.…”
Section: Discussionmentioning
confidence: 88%